Molecular Mechanisms of HBV-Associated Hepatocarcinogenesis - Guerrieri, Francesca; Belloni, Laura; Pediconi, Natalia; Levrero, Massimo (Seminars in Liver Disease, 2013)
Hepatitis B virus (HBV) contributes to hepatocellular carcinoma (HCC) development through direct and indirect mechanisms. HBV-DNA integration into the host genome occurs at early steps of clonal tumor expansion and induces both genomic instability and direct insertional mutagenesis of diverse cancer-related genes. Prolonged expression of the viral regulatory protein HBx and the large envelope protein deregulate the cellular transcription program and proliferation control and sensitize liver cells to carcinogenic factors. Epigenetic changes targeting the expression of tumor suppressor genes occur early in the development of HCC. A major role is played by HBx that is recruited on cellular chromatin and modulates chromatin dynamics at specific gene loci. Compared with tumors associated with other risk factors, HBV-related tumors have a higher rate of chromosomal alterations and p53 inactivation by mutations, overexpress fetal liver/hepatic progenitor cells genes, and show a specific activation of the AKT pathway. The wnt/β-catenin pathway is also often activated, but HBV-related tumors display a low rate of activating β-catenin mutations. All available evidence strongly supports the notion that chronic HBV infection triggers both common and etiology-specific oncogenic pathways, thus playing a direct role beyond stimulation of host immune responses and chronic necroinflammatory liver disease.
Keywords: hepatocellular carcinoma (HCC); hepatitis B virus (HBV); HBx protein; epigenetics; miRNAs